Wali Asuh Counseling Service Program to Create Santri’s Independent at al-Hasyimiyah Region of Nurul Jadid Islamic Institute Paiton Probolinggo - Santoso, Agus; Mu’minin, Ummahatul (Proceedings of International Conference on Da'wa and Communication, 2019)
This research has two problems of study, both are (1) how is the process of implementing wali asuh counseling service program to create santri’s independent at Al Hasyimiyah Region of Nurul Jadid Islamic Institute Paiton Probolinggo (2) how is the result of implementing wali asuh counseling service program to create santri’s independent at Al Hasyimiyah Region of Nurul Jadid Islamic Institute Paiton Probolinggo. The researcher used qualitative research methods with a case study format. Qualitative data is obtained by interview, observation, and documentation. The results of this research are (1) Implementation of wali asuh counseling service program through seven services, namely orientation, information, placement and distribution, tutoring, individual counseling, group guidance, and group counseling. (2) While, the results of implementing this program through seven services of counseling are independent santri who have a religious, dynamic, and social personality.